The Impact of the Implementation of Sharia Good Corporate Governance on Financial Performance at Bank Syariah Indonesia KCP Binjai - Haryani, Pipit; Barus, Elida Elfi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the effect of Sharia Good Corporate Governance (GCG) implementation on the financial performance of Bank Syariah Indonesia (BSI) Kantor Cabang Pembantu (KCP) Binjai. The research employs a quantitative approach with an associative method. Primary data were collected through questionnaires distributed to all employees of BSI KCP Binjai, while secondary data were obtained from financial statements and GCG reports for the period 2022–2024. The independent variable is Sharia GCG implementation, measured through six dimensions: transparency, accountability, responsibility, independence, fairness, and Sharia compliance. The dependent variable is financial performance, proxied by Return on Assets (ROA). Data were analyzed using multiple linear regression. The results indicate that, simultaneously, Sharia GCG implementation has a significant effect on the financial performance of BSI KCP Binjai. Partially, transparency, accountability, independence, fairness, and Sharia compliance have positive and significant effects on ROA, while responsibility shows a positive but insignificant effect. Sharia compliance is identified as the most dominant factor influencing financial performance. These findings highlight that effective Sharia GCG implementation serves as a strategic mechanism to enhance financial performance and strengthen public trust in Islamic banking institutions.